The RESEARCH URGENCY: BASED ON LITERATURE REVIEW OF BASIC CONCEPTS OF SCIENCE AND SOURCES OF KNOWLEDGE: URGENSI PENELITIAN: BERDASARKAN KAJIAN PUSTAKA ATAS KONSEP DASAR ILMU DAN SUMBER PENGETAHUAN - Adrias, Adrias; Arfiyanti, Riskha; Latifah, Nafsi; Sayfullooh, Istiqomah As (Cerdas Proklamator, 2024)
Science plays a crucial role in the development of society and the formation of human civilization. This article discusses the urgency of understanding the basic concepts of science and the research process, as well as the side effects of various alternative sources of knowledge other than research. It uses the literature study method to explore current information on the scientific process, including the role of the scientific community, and discusses alternative sources of knowledge such as authority, tradition, common sense, media and personal experience. The findings show that while alternative sources can provide knowledge, they often have limitations that can affect the accuracy of knowledge. Therefore, it is important to emphasize the urgency of research and critical thinking for both academia and society in general. In addition, interdisciplinary collaboration and education on scientific validation are also important to reduce information distortion and strengthen the foundation of knowledge.